Stress analysis of a bolted finite dimensions plate under bearing-bypass load interaction using the Airy stress function. (1st April 2022) - Nguyen-Hoang, M.; Becker, W.
Abstract: Bolted joints are frequently used to connect rather thin parts in lightweight structures, e.g. air- and spacecraft. This is also motivated by inexpensive manufacturing and the ability to disassemble. However, holes need to be drilled and stress concentrations arise. Usually, multiple bolts/rows of bolts are placed. Then, the load is partly introduced into one bolt while the remaining rest stays in the plate. This problem setting is also referred to as bolted joint under combined bearing-bypass load. When there are negligible secondary bending effects a 2D model can be employed. Further, a linear approach without contact elasticity is commonly chosen, which is provided by superimposing the open- and pin-loaded hole/filled-hole problem. The latter is then idealised by sinusoidal radial tractions along half of the hole edge. The structural assessment shall be done using precise analysis means since safety-critical parts are connected by bolted joints. These means can be based on analytical methods, which are beneficial in terms of computational effort and shall be scope of the present paper. For stress field representation, use is made of the Airy stress function method. First, the solutions of the special cases open and filled hole are determined. These are then superimposed. Finite plate dimensions are taken into account using auxiliary and correction stress functions, which are based on a novel periodic arrangement technique. Effects of raised stress concentrations due to finite dimensions as well as the ratio between bearing and bypass load are extensively discussed. Validation by means of Finite Element analyses reveals excellent agreement. Highlights: Stress analysis of finite dimensions bolted joints under bearing-bypass load. Airy stress functions for stress state representation. Finite plate dimensions captured. Good agreement to Finite Element analyses.